Primary hemifacial spasm: a neurophysiological study. Issue 1 (January 1986) - Esteban, A; Molina-Negro, P
Abstract : A series of 53 cases of primary hemifacial spasm have been evaluated by means of blink reflexes and their results compared with a normal control group. Reflex responses were obtained by percutaneous electrical stimulus of both the supraorbital nerve (trigemino-facial reflex), and the facial nerve at the stylo-mastoid region (facio-facial reflex). The R2 response was considered abnormal when its latency was shortened (hyperactivity) or delayed (hypoactivity). Thirty-six out of 53 cases with primary hemifacial spasm showed abnormal responses, with a combination of facial nerve impairment (delayed R2 in the facio-facial reflex) and trigeminal-facial hyperactivity (shortened R2 in the trigemino-facial reflex). Five cases showed hyperactivity in both the trigemino-facial reflex and the facio-facial reflex reflexes. These results suggest a state of hyperexcitability, probably at the level of the facial nucleus, combined with a peripheral facial nerve involvement in a high proportion of patients with primary hemifacial spasm.